Religion in the new Europe - Michalski, Krzysztof, 1948-2013 (Conditions of European solidarity, 2006)
Since the signing of the Treaty of Rome initiating the ongoing process of European integration in 1957, Western European societies have undergone a rapid, drastic and seemingly irreversible process of secularization. In this respect, one can talk of the emergence of a post-Christian Europe. At the same time, the eastward expansion of the European Union and the drafting of a European constitution have triggered fundamental questions concerning European identity and the role of Christianity in that identity. The most controversial and anxiety-producing issues, which are rarely confronted openly, are the potential integration of Turkey and the potential integration of non-European immigrants, who in most European countries happen to be overwhelmingly Muslim. The reintegration of Catholic Poland into secular Europe can also be viewed as "a difficult challenge." (And/or as "a great apostolic assignment") It is the interrelation between these phenomena that the essays in the book, written upon the invitation by the previous President of the European Union, Romano Prodi, seek to explore